Antimicrobial Treatment of Staphylococcus aureus in Patients With Cystic Fibrosis - Esposito, Susanna; Pennoni, Guido; Mencarini, Valeria; Palladino, Nicola; Peccini, Laura; Principi, Nicola (Frontiers in Pharmacology, 2019)
Staphylococcus aureus is a ubiquitous human commensal pathogen. It is commonly isolated in cystic fibrosis (CF) patients and is considered one of the main causes of the recurrent acute pulmonary infections and progressive decline in lung function that characterize this inherited life-threatening multisystem disorder. However, the true role of S. aureus in CF patients is not completely understood. The main aim of this narrative review is to discuss the present knowledge of the antimicrobial treatment of S. aureus in CF patients. Literature review showed that despite the fact that the availability and use of drugs effective against S. aureus has coincided with a significant improvement in the prognosis of lung disease in CF patients, clearly evidencing the importance of S. aureus therapy, how to use old and new drugs to obtain the maximal effectiveness has not been precisely defined. The most important problem remains that the high frequency with which S. aureus is carried in healthy subjects prevents the differentiation of simple colonization from infection. Moreover, although experts recommend antibiotic administration in CF patients with symptoms and in those with persistent detection of S. aureus, the best antibiotic approach has not been defined. All these problems are complicated by the evidence that the most effective antibiotic against methicillin-resistant S. aureus (MRSA) cannot be used in patients with CF with the same schedules used in patients without CF. Further studies are needed to solve these problems and to assure CF patients the highest level of care.